Implementation of School Literacy Program in Islamic Religious Education Learning: Implementasi Program Literasi Sekolah dalam Pembelajaran Pendidikan Agama Islam - Khoridatunnida, Khoridatunnida; Azhari, Muhammad (Universitas Muhammadiyah Sidoarjo, 2025)
This study analyzes the implementation of the School Literacy Movement (GELAS) in Islamic religious education to improve students' ability to read and write the Qur'an. It focuses on the effectiveness of GELAS and the supporting and inhibiting factors in its application. Using a qualitative descriptive method, data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman's model: data reduction, data display, and conclusion drawing. The results show that GELAS has been implemented smoothly through activities like libraries, reading corners, morning gatherings, 15-minute Qur'an reading sessions, and weekly Yasin reading. Supporting factors include adequate facilities, active school participation, and teacher supervision. Inhibiting factors include limited funding and low student motivation. Highlights: Focuses on the effectiveness of GELAS in Qur'an literacy. Uses qualitative methods: observation, interviews, documentation. Finds success supported by facilities, but hindered by low student motivation. Keywords: School Literacy Movement, Islamic Religious Education, Qur'an Literacy, GELAS Program, Student Motivation